1992
DOI: 10.1159/000284769
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Attributional Style and the Dexamethasone Suppression Test: Relationship to the Endogenous/Melancholic Distinction and to Each Other

Abstract: The dexamethasone suppression test (DST) and the depressive attributional style questionnaire (ASQ) were administered to 105 depressed patients prior to participation in a double-blind outpatient study and to 29 normal controls. The depressed patients were classified into three groups (1) met criteria for both research diagnostic criteria for definite endogenous depression and DSM III melancholia; (2) met criteria for neither, and (3) met criteria for one but not both. The group that met criteria for both RDC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The ASQ-F's alpha internal consistency (.72) and 5-week retest reliability (.64) have been adequate in past research (Peterson et al, 1982). Validity is supported through moderate correlations with self-report measures of depressive symptoms and self-concept (Tennen, Herzberger, & Nelson, 1987) and higher scores in depressed individuals compared with controls (Peselow & Fieve, 1992). Alpha internal consistency was.89 and.91 in the atypical and recurrent depression data sets, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The ASQ-F's alpha internal consistency (.72) and 5-week retest reliability (.64) have been adequate in past research (Peterson et al, 1982). Validity is supported through moderate correlations with self-report measures of depressive symptoms and self-concept (Tennen, Herzberger, & Nelson, 1987) and higher scores in depressed individuals compared with controls (Peselow & Fieve, 1992). Alpha internal consistency was.89 and.91 in the atypical and recurrent depression data sets, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We pooled data using methods summarized by Kendall and Sheldrick (2000) that weight studies' mean and standard deviation statistics by sample size to derive a population estimate. We pooled data from three reports (Fear, Sharp, & Healy, 1996; Heimberg et al, 1989; Jack & Williams, 1991) to derive SUCC norms ( M = 4.78, SD = 0.59) and from these reports plus three additional reports (Eaves & Rush, 1984; Peselow & Fieve, 1992; Zimmerman, Coryell, Corenthal, & Wilson, 1986) to derive FAIL norms ( M = 3.94, SD = 0.62). For the SEF, we used norms from a large representative sample in the United States ( M = 90.62, SD = 12.65; Lansford et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Contributing to the debate about the correct classification, or the ability of a certain definition of melancholia to identify non-suppressors, Peselow et al (1992) demonstrated that patients who met both DSM-III criteria for melancholia and RDC criteria for endogenous depression, showed higher rates on non-suppression than those with «neither» subtype and controls, but not compared to those with «either of» the subtypes (Peselow et al, 1992). Paslakis et al (2011) also used DSM-IV (SCID-validated) criteria for melancholia, and although they did demonstrate a significant difference in suppression levels between melancholic depressed patients and controls, both the mean effect size and the sensitivity of the test proved low (Paslakis et al, 2011).…”
Section: Dexamethasone Suppression Testmentioning
confidence: 99%